Occupational exposure to nickel and hexavalent chromium and the risk of lung cancer in a pooled analysis of case‐control studies (SYNERGY). Issue 4 (23rd September 2022) - Behrens, Thomas; Ge, Calvin; Vermeulen, Roel; Kendzia, Benjamin; Olsson, Ann; Schüz, Joachim; Kromhout, Hans; Pesch, Beate; Peters, Susan; Portengen, Lützen; Gustavsson, Per; Mirabelli, Dario; et al.
Abstract: There is limited evidence regarding the exposure‐effect relationship between lung‐cancer risk and hexavalent chromium (Cr(VI)) or nickel. We estimated lung‐cancer risks in relation to quantitative indices of occupational exposure to Cr(VI) and nickel and their interaction with smoking habits. We pooled 14 case‐control studies from Europe and Canada, including 16 901 lung‐cancer cases and 20 965 control subjects. A measurement‐based job‐exposure‐matrix estimated job‐year‐region specific exposure levels to Cr(VI) and nickel, which were linked to the subjects' occupational histories. Odds ratios (OR) and associated 95% confidence intervals (CI) were calculated by unconditional logistic regression, adjusting for study, age group, smoking habits and exposure to other occupational lung carcinogens. Due to their high correlation, we refrained from mutually adjusting for Cr(VI) and nickel independently. In men, ORs for the highest quartile of cumulative exposure to CR(VI) were 1.32 (95% CI 1.19‐1.47) and 1.29 (95% CI 1.15‐1.45) in relation to nickel. Analogous results among women were: 1.04 (95% CI 0.48‐2.24) and 1.29 (95% CI 0.60‐2.86), respectively. In men, excess lung‐cancer risks due to occupational Cr(VI) and nickel exposure were also observed in each stratum of never, former and current smokers. Joint effects of Cr(VI) and nickel with smoking were in general greater than additive, but not different from multiplicative. In summary, relatively low cumulative levels of occupational exposure to Cr(VI) and nickel were associated with increased ORs for lung cancer, particularly in men. However, we cannot rule out a combined classical measurement and Berkson‐type of error structure, which may cause differential bias of risk estimates. Abstract : What's new? Occupational exposure to hexavalent chromium (Cr(VI)) and nickel is associated with increased lung‐cancer risk. Little is known, however, about quantitative exposure‐effect relationships between lung cancer and Cr(VI) or nickel. Here, quantitative exposure‐effect relationships were investigated using secondary measurement data from different regions and time periods across a wide range of jobs, with adjustment for smoking habits. Lung‐cancer risk was elevated even at low cumulative exposure levels to Cr(VI) or nickel, particularly in men and regardless of smoking habits. The findings warrant ongoing surveillance for carcinogenic risks of occupational metal exposure.